Concentration of complex Zn+2–chelator around blood vessels in pancreatic islets result alteration and destruction of capillaries - Meyramov, G.G.; Kohnert, K.-D.; Williams, A.A.; Kikimbaeva, A.A.; Turgunova, L.G.; Tyrzhanova, S.S.; Alina, A.R.; Shaybek, A.Zh.; Abdullina, G.A.; Zhuzbaeva, G.O.; Kovalenko, O.L.; Meyramova, A.G. (Pub KSU, 2014)
Authors showed that concentration around capillaries wall of complex Zn+2-chelator formed in result of interaction in cytoplasm of B-cells of Zn+2-ions with diabetogenic zincbinding chelators is one of causes of developed vascular changes in capillaries of pancreatic islets. These changes as alteration of basal membrane of capillaries, edema of endothelium, partial destruction of capillaries wall and hyperemia can to aggravate developing of degenerative changes in pancreatic islets induced by Zn+2-chelator that result aggravation developing of diabetes. Meanwhile main cause of developing of diabetes induced by zincbinding chelators is its ability to form toxic complexes with Zn+2-ions in B-cells that result necrosis and destruction of B-cells within short time.
Қылтамырлар қабырғасының бұзылуымен қоса жүретін панкреатиттік аралшықтардағы қылтамырлар маңайындағы «Zn+2–хелатор» кешенінің қалыптасуы
Формирование комплекса «Zn+2–хелатор» вокруг капилляров в панкреатических островках, сопровождающееся деструкцией их стенки
Keywords: pancreatic islets; insulin, Zn+2-ions; B-cells; destruction; blood vessel; chelat complexes; vascular changes; diabetogenic derivatives of 8-oxyquinolin